1990
DOI: 10.1007/bf00180652
|View full text |Cite
|
Sign up to set email alerts
|

Different muscarinic receptors mediate autoinhibition of acetylcholine release and vagally-induced vasoconstriction in the rat isolated perfused heart

Abstract: Experiments were carried out on rat isolated perfused hearts with both vagus nerves attached. The acetylcholine stores were labelled with [14C]-choline. The effects of muscarinic receptor antagonists on the [14C]-overflow and increase in perfusion pressure evoked by vagus nerve stimulation (10 Hz, 4-10 mA) were studied in order to determine the muscarinic receptor type involved in autoinhibition of acetylcholine release and vagally-induced vasoconstriction in the rat heart. Stimulation of the vagus nerves (120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The electrically evoked overflow of total 3 H-(or 14 C-) compounds from parasympathetically innervated tissues preincubated with 3 H-(or 14 C-) choline is a measure of action potential-evoked neuronal release of 3 H-( 14 C-) acetylcholine (studies summarized in Tables 6 and 7 of Starke et al 1989; recent studies in heart: Bognar et al 1990a;Dawson et al 1996;Oberhauser et al 2001;in bladder: Somogyi et al 1994;D'Agostino et al 1997D'Agostino et al , 2000Tobin and Sjögren 1998). In accord with this view, the electrically evoked overflow of tritium in the present experiments was greatly reduced by tetrodotoxin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrically evoked overflow of total 3 H-(or 14 C-) compounds from parasympathetically innervated tissues preincubated with 3 H-(or 14 C-) choline is a measure of action potential-evoked neuronal release of 3 H-( 14 C-) acetylcholine (studies summarized in Tables 6 and 7 of Starke et al 1989; recent studies in heart: Bognar et al 1990a;Dawson et al 1996;Oberhauser et al 2001;in bladder: Somogyi et al 1994;D'Agostino et al 1997D'Agostino et al , 2000Tobin and Sjögren 1998). In accord with this view, the electrically evoked overflow of tritium in the present experiments was greatly reduced by tetrodotoxin.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have not always yielded uniform and unambiguous results. Several studies suggested that the inhibitory autoreceptors are M 2 in the rat heart (Bognar et al 1990a) and trachea (Aas and Maclagan 1990), the guinea-pig iris (Bognar et al 1990b), the rabbit urinary bladder Sjögren 1995, 1998) and the human heart (Oberhauser et al 2001). On the other hand it has been proposed that the inhibitory autoreceptors are M 1 in the chicken heart (Brehm et al 1992) and the circular muscle of the guinea-pig ileum (Dietrich and Kilbinger 1995), M 4 in the guinea-pig urinary bladder (Alberts 1995), both M 1 and M 2 in the guinea-pig stomach (Ogishima et al 2000), and both M 2 and M 3 in bovine cerebral arteries (Ferrer et al 1992).…”
Section: Introductionmentioning
confidence: 98%
“…In baboons, application of low concentrations of acetylcholine and efferent vagus stimulation results in vasodilatation, while more intense stimulation produces vasoconstriction [25,44]. Vagal stimulation only elicits atropinesensitive vasoconstriction in isolated rat hearts [4,42], and periarterial electrical stimulation of bovine and human myocardial flaps also results in vasoconstriction [22]. Thus, marked species differences have been observed with respect to the atropine-sensitive responses to parasympathetic stimulation in the coronary circulation [14,22].…”
Section: Introductionmentioning
confidence: 91%
“…Thus, infused acetylcholine suppresses the release of acetylcholine, noradrenaline, and neuropeptide Y in the guinea-pig heart [4,11,20] and the release of noradrenaline, nitric oxide and vasoactive intestinal peptide in isolated arteries [1,8,21,28]. The receptors mediating the prejunctional inhibitory effect of acetylcholine have been characterized as muscarinic M 2 -receptors in most vascular preparations [12].…”
Section: Interaction Of Acetylcholine With Other Neurotransmittersmentioning
confidence: 97%
“…Vagal stimulation produced coronary vasoconstriction in the rat heart (Van Charldorp et al, 1987;Bognar et al, 1990), and periarterial electrical stimulation of cattle isolated perfused heart (Kalsner, 1979) or human myocardial slabs in vitro induced an atropine-sensitive vasoconstriction (Kalsner, 1989). In contrast, efferent stimulation of the vagal nerves or activation of reflex mechanisms in the dog produced coronary vasodilatation (Feigl, 1969;Hackett et al, 1972;Ito et al, 1985;Van Winkle & Feigl, 1989).…”
Section: Introductionmentioning
confidence: 99%